LEVEL OF PHYSICAL ACTIVITY OF SECONDARY SCHOOL STUDENTS IN KOSOVO - Abedin Ibrahimi; Vildane Jashari; Ismajl Jashari (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The results of empirical research survey presented in this paper suggest that the level of physical activity observed high school students at a relatively high level. More detailed analysis showed that the sources of these activities - mostly spontaneous and economic and recreational hobby activities, unreliable supports for regular physical activity coordinated with the health standard set by the Centers for Disease Control and Prevention and the American College of Sports Medicine.